Hospital Religious Affiliation and Emergency Contraceptive Prescribing Practices - Rubin, Susan E. (© American Journal of Public Health 2006, 2006)
With access to reproductive health care eroding, examination of prescribing of contraception, including emergency contraception (EC), is important. We examined whether working in a family practice affiliated with a religious institution changes the likelihood of a provider prescribing EC. Our survey asked about EC prescribing practices in a range of situations. As predicted, practitioners in non–religiously affiliated practices reported higher rates of prescribing EC than those in religiously affiliated practices. In both cases, however, the practitioners’ prescribing patterns were inadequate.